Theoretical and Experimental Comparisons of Total Solar Transmittance for Polycarbonate Sheet with Twin Wall Rectangular Structure - Zbigniew Zapałowicz; Agnieszka Garnysz-Rachtan (Applied Mechanics, 2022)
Multiwall polycarbonate sheets are applied as construction elements. Modelling and analysis of thermal processes that occur in this material demand the knowledge of solar transmittance. Values of this parameter determined in laboratory conditions are given in the technical specification of the product. However, the parameter is in practice a complex function depending on the number of factors. This paper presents theoretical and experimental research results for total solar transmittance (TST) for a polycarbonate sheet with twin wall rectangular structure. Theoretical TST is calculated as a product of transmissivity after accounting for light absorption in polycarbonate and of transmissivity after accounting for multiple reflections of solar rays from walls of a channel. The first kind of transmissivity is insignificant and can be neglected. The second one depends on the number of reflection layers, season, and time of day. Experimental TST is determined as the ratio of irradiance under and above the polycarbonate sheet measured by pyranometers. Experimental TST is also a function of time of day and season. Both kinds of TST have an approximately constant value in the time about noon. The theoretical values of TST (0.74) are approximately equal to experimental values of TST (0.75) for the selected summer day. The value of TST in catalogue is equal to 0.82.